A comparison study of TCP protocol (RENO and SACK) in WLAN, LAN networks - Mahmood, Omar Shakir (2018)
Todays, in order to compete with fast-growing companies, the demand for effective, efficient, and reliable access to data has rapidly increased, mainly by storing large amounts of information in computers that can manage this data electronically, rather than file cabinets and file mountains. Computer network technology is the glue that binds these elements together. Transport Control Protocol (TCP) is a connectionoriented protocol of the transport layer. This protocol supports some features such as reliability, flow control, and congestion control, TCP was designed to serve wired connection, thus it assumes that all the packets are lost in the network because of the congestion. While the wireless medium is more exposed to transmission errors and sudden changes. The main goal of this project is to evaluate various versions of TCP protocols in (LAN) and a (WLAN) networks. Simulation experiments are done using Simulation Network (NS2) programs for TCP Sack protocol and TCP Reno protocol for WLAN and LAN networks. In this project, the study performance metrics examined are network throughput, network congestion window ( cwnd), and packet loss. Simulation experimental results have shown that the better TCP Reno has the better performance than TCP Sack in LAN network. Conversely, The TCP Sack showed better performances than TCP Reno in WLAN network.